Penerapan Analisis Swot Terhadap Penentuan Strategi Pemasaran Dalam Meningkatkan Kualitas Pelayanan di Gerai Mixue Golden City - Puteri, Risqina; H, Hadita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Every business must respond quickly to keep up with developments and the development of various fields in the current and future eras of globalization. Companies in the fields of production, marketing, and sales must have effective strategies to handle the challenges that will come. This research aims to show how the marketing strategy at Mixue Golden City Outlets improves service quality based on SWOT analysis. This research uses qualitative analysis methods. Qualitative data consists of interview results, field notes, and original documents. The data used comes from two sources, namely, primary data sources and secondary data. In this research, it provides information that a company like Mixue Golden City not only has strengths and opportunities but also has weaknesses and threats, based on the results of the SWOT analysis that has been carried out and internal factors, namely strengths: Mixue has quite good production quality and a good taste. delicious, and the price is quite affordable. Weaknesses: Mixue has sometimes inconsistent human resource quality, the latest innovations are only available at certain times; and it does not provide or sell snacks. And from external factors, namely opportunities : mixing partnerships with local producers and creating new flavors and new ice cream models. Threats: having many competitors, decreasing people's purchasing power, and increasing raw material prices.